2016
DOI: 10.5665/sleep.5972
|View full text |Cite
|
Sign up to set email alerts
|

The National Veteran Sleep Disorder Study: Descriptive Epidemiology and Secular Trends, 2000–2010

Abstract: A commentary on this article appears in this issue on page 1331.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
134
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 89 publications
(114 reference statements)
4
134
0
Order By: Relevance
“…In April 2015, the Veterans Health Administration (VA) approved the use of HGNS for the nine million veterans receiving health care in the VA system . This decision was based on research indicating a steadily increasing incidence of OSA in US veterans; most recent estimates show that the prevalence of OSA among veterans treated in the VA system ranges from 3% to 8% .…”
Section: Introductionmentioning
confidence: 99%
“…In April 2015, the Veterans Health Administration (VA) approved the use of HGNS for the nine million veterans receiving health care in the VA system . This decision was based on research indicating a steadily increasing incidence of OSA in US veterans; most recent estimates show that the prevalence of OSA among veterans treated in the VA system ranges from 3% to 8% .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2011, Hughes, Jouldjian, Washington, Alessi, and Martin (2013) have reported that women veterans with insomnia have higher rates of posttraumatic stress disorder, and a recent publication based on the Women’s Health Initiative reported that women veterans had similar overall rates of insomnia compared with nonveteran women (30.5% vs. 30.8%, respectively), but women veterans had higher risk for insomnia co-occurring with sleep apnea risk factors (Rissling et al, 2016). Recently, changes in rates of diagnosed sleep disorders among more than 9,000,000 VA users was described by Alexander et al (2016). Rates of diagnosed insomnia differed between men and women who receive VA care; however, these differences were not consistent across fiscal years.…”
mentioning
confidence: 99%
“…At-home sleep monitoring may useful in detecting previously undetected sleep apnea and thereby facilitate its treatment. Assessing insomnia and apnea in Veterans is particularly crucial given recent documentation that over the decade from 2000-2010, sleep disorder prevalence rose 6-fold in those seeking care in Veteran's Administration (VA) facilities 3 .…”
Section: Sleep Disorders In Veteransmentioning
confidence: 99%